The protective effects of dietary Clostridium butyricum supplementation on hepatic ischemia reperfusion injury in rats - Yang,Xuan (2022)
ABSTRACT Purpose: This study investigated the effects of oral administration of Clostridium butyricum (C. butyricum) on inflammation, oxidative stress, and gut flora in rats with hepatic ischemia reperfusion injury (HIRI). Methods: The rats from C. butyricum group were given C. butyricum for 5 days. Then, hepatic ischemia for 30 min and reperfusion for 6 h were performed in all the rats. After the animals were sacrificed, alanine transaminase (ALT), aspartate aminotransferase (AST), lipopolysaccharide (LPS) in serum, short-chain fatty acids (SCFAs), and gut microbiota composition in feces, and malondialdehyde (MDA), glutathione (GSH), tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), Toll-like receptor 4 (TLR4), nuclear factor-kappa Bp65 (NF-κBp65) and histological analysis in the liver were performed. Results: The rats given C. butyricum showed decreased ALT, AST, LPS, and MDA; improved GSH and histological damage; changes in SCFAs; declined TNF-α, IL-6, TLR4, and pNF-κBp65/NF-κBp65; and changes in the gut microbial composition, which decreased the Firmicutes/Bacteroidetes ratio and increased the relative abundance (RA) of probiotics. Conclusions: C. butyricum supplementation protected against HIRI by regulating gut microbial composition, which contributed to the decreased LPS and attenuation of inflammation and oxidative stress. These indicate C. butyricum may be a potent clinical preoperative dietary supplement for HIRI.